Tingkat Pengetahuan Siswa Terhadap Permainan Futsal Sekolah Menengah Atas - Zein, Fajar Rahman; Iqbal, Rahmat; Abdulloh, Abdulloh (Jurnal Ilmiah Wahana Pendidikan, 2023)
The problem of this research is how high is the knowledge of students in high school futsal games. The aim of this study is to find out how high the knowledge of students in high school futsal games. The survey is the method used in this study and uses a quantitative approach. The sample used was 197 students using the total sampling technique. The data collection technique used in this study was a survey technique, using a questionnaire by distributing questionnaires on the level of knowledge of futsal games. From the results of this study it is known that the level of students' knowledge of the game of futsal states in the "very high" category with a percentage of 27.9%, in the "high" category with a percentage of 65.5%, in the "moderate" category with a percentage of 6.1%, in the "low" category with a percentage of 0%, in the "very low" category with a percentage of 0.5%. So it can be concluded that the level of knowledge of students in high school futsal games is high.